Pro-apoptotic and anti-angiogenic actions of 2-methoxyestradiol and docosahexaenoic acid, the biologically derived active compounds from flaxseed diet, in preventing ovarian cancer - Purab Pal; Karen Hales; Jim Petrik; Dale Buchanan Hales (BMC, 2019)
Abstract Background We have previously shown that a whole flaxseed supplemented diet decreased the onset and severity of ovarian cancer in the laying hen, the only known animal model of spontaneous ovarian cancer. Flaxseed is rich in omega-3 fatty acids (OM3FA), mostly α-Linoleic acid (ALA), which gets converted to Docosahexaenoic acid (DHA) by the action of delta-6 desaturase enzyme. Ingestion of flaxseed also causes an increase in production of 2-methoxyestradiol (2MeOE2) via the induction of the CYP1A1 pathway of estrogen metabolism. We have previously reported that the flaxseed diet induces apoptosis via p38-MAPK pathway in chicken tumors. The objective of this study was to investigate the effect of the flaxseed diet on ovarian cancer in chickens, focusing on two hallmarks of cancer, apoptosis and angiogenesis. Results The anti-cancer effects of two active biologically derived compounds of flax diet, 2MeOE2 and DHA, were individually tested on human ovarian cancer cells and in vivo by the Chick Chorioallantoic Membrane (CAM) assay. Our results indicate that a flaxseed-supplemented diet promotes apoptosis and inhibits angiogenesis in chicken tumors but not in normal ovaries. 2MeOE2 promotes apoptosis in human ovarian cancer cells, inhibits angiogenesis on CAM and its actions are dependent on the p38-MAPK pathway. DHA does not have any pro-apoptotic effect on human ovarian cancer cells but has strong anti-angiogenic effects as seen on CAM, but not dependent on the p38-MAPK pathway. Conclusions Dietary flaxseed supplementation promotes a pro-apoptotic and anti-angiogenic effect in ovarian tumors, not in normal ovaries. The biologically derived active compounds from flaxseed diet act through different pathways to elicit their respective anti-cancer effects. A flaxseed-supplemented diet is a promising approach for prevention of ovarian cancer as well as having a significant potential as an adjuvant treatment to supplement chemotherapeutic agents for treatment of advanced stages of ovarian cancer.